Samorząd akademicki a wolność nauki - Wykrętowicz, Stanisław (Academic self government and the freedom of science, 2006)
In the literature on the subject, the notion of a self government is not explicitly perceived. Whai interests us here is a concept of a self government in the meaning of the theory of the administrative law. The legal notion of a self government takes account of only those organizations of citizens, which function within the system of the public law and hold - by law - administrative authority and obligatory membership. In the process of developing of a citizen society, two types of self government have been formed: a corporative and an institutional one, the latter being the academic self government. The aim of this work is to bring closer to readers the very essence of such a self government, thoroughly linked to a liberal model of a University as an autonomous public institution, to define the scope of its independence from the government administration and its impact on the freedom and development of science. In Poland during the transformation time universities do not have academic self government and science is still under control of the government administration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 49-62